2019
DOI: 10.1681/asn.2019030218
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Diabetic Kidney Disease Highlights Biology Involved in Glomerular Basement Membrane Collagen

Abstract: BackgroundAlthough diabetic kidney disease demonstrates both familial clustering and single nucleotide polymorphism heritability, the specific genetic factors influencing risk remain largely unknown.MethodsTo identify genetic variants predisposing to diabetic kidney disease, we performed genome-wide association study (GWAS) analyses. Through collaboration with the Diabetes Nephropathy Collaborative Research Initiative, we assembled a large collection of type 1 diabetes cohorts with harmonized diabetic kidney d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
184
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(191 citation statements)
references
References 83 publications
6
184
1
Order By: Relevance
“…This result confirmed that individual gene data derived from the single cell transcriptomic experiment could be independently validated, with spatial resolution, bolstering the validity of the conclusions drawn by computational analyses. Furthermore, these data highlight that the key response to injury by a specific population of podocytes is to upregulate collagen production, which may account for the prominent or thick GBM observed in progressive diseases such as DKD (27).…”
Section: Disease-associated Gene Programs Identified In Specific Podomentioning
confidence: 88%
See 1 more Smart Citation
“…This result confirmed that individual gene data derived from the single cell transcriptomic experiment could be independently validated, with spatial resolution, bolstering the validity of the conclusions drawn by computational analyses. Furthermore, these data highlight that the key response to injury by a specific population of podocytes is to upregulate collagen production, which may account for the prominent or thick GBM observed in progressive diseases such as DKD (27).…”
Section: Disease-associated Gene Programs Identified In Specific Podomentioning
confidence: 88%
“…One of the critical components of the GBM is collagen type IV 5 (Col4a5); mutations in this gene cause Alport syndrome and FSGS in humans (25,26). Variants in Col4a3, another structural component of the GBM, were recently identified by a comprehensive genome wide association study (GWAS) in diabetic kidney disease (DKD) (27).…”
Section: Disease-associated Gene Programs Identified In Specific Podomentioning
confidence: 99%
“…Although the link between genetic variants encoding type IV collagen chains and rare kidney disease is well established, recent large genetic cohort studies suggest COL4A genes have a role in diseases that are much more common. Variants in COL4A genes have been found to be associated with CKD, diabetic nephropathy, cardiovascular disease, and stroke (38)(39)(40)(41)(42). This is perhaps representative of the organ-specific function of basement membranes and the role of the different type IV collagen isoforms.…”
Section: Basement Membrane Genesmentioning
confidence: 99%
“…As a member of the TGF-b family, BMP-7 was first speculated to be a pro-fibrotic factor, but recently an abundance of research presented a strong anti-fibrotic, anti-inflammatory and antiapoptotic effect. BMP-7 was identified as one of potential genes for DN in the most recent genome-wide association study in the Juvenile Diabetes Research Foundation Diabetic Nephropathy Collaborative Research Initiative, which has assembled 20,000 participants with type 1 diabetes, with and without DKD 37 . Earlier, a proteomic analysis carried in type 2 diabetes patients from the ADVANCE trial, showed a graded increase in the risk of CKD in individuals with lower circulating BMP-7 levels or significantly higher TGF-b1 levels 38 .…”
Section: Human Studies Of Protective Factors For Renal Function Lossmentioning
confidence: 99%